(untitled) (Portuguese Journal of Family Medicine and General Practice, 2016)
Benign acute childhood myositis (BACM) is an uncommon, disabling, self-limited disease that is relatively unknown by healthcare providers. This article reports a case of BACM in a 6 year-old child who suffered from calf pain and was unable to bear weight after an upper respiratory tract infection. There was no history of trauma and there were no similar episodes in the past. Because of its excellent prognosis, increased awareness by primary care health care providers is needed, to permit safe follow up in most cases